Perlindungan Hukum Terhadap Hak Upah Pekerja Akibat Perusahaan Telah Dinyatakan Pailit - Arbi Dalimunthe; Didik Suhariyanto; Dewi Iryani (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Bankruptcy is a legal process in which the assets of an insolvent debtor are managed and settled by a curator under the supervision of a judge. This research discusses the legal certainty for workers when the company goes bankrupt, as well as the legal protection for their rights. It employs normative legal research methods and qualitative analysis of secondary data, which includes primary, secondary, and tertiary legal materials. The results of this study indicate that workers' rights must be prioritized in cases of company bankruptcy, in accordance with Constitutional Court Decision No. 67/PUU-XI/2013. In such instances, unpaid workers' wages must take precedence over other creditors, including the state and government agencies. Curators play an important role in protecting workers' rights during the insolvency process, and workers have the right to sue if their rights are not met.